Barbarians and Civilization in International Relations - Mark B. Salter (www.plutobooks.com, 2002)
In the greater clash, the global ‘real clash’, between civilization and barbarism, the world’s great civilizations, with their rich accomplishments in religion, art, literature, philosophy, science, morality, and compassion, will hang together or hang separately.1 Huntington’s invocation of the clash between civilization – read as high culture – and barbarism illustrates the function of these terms as identity groups and the connections between identity, culture, civilization and barbarism. IDENTITY The concept of ‘identity’ is clouded in epistemological battles, academic wrangling and definitional ambiguity. Despite this conceptual ambiguity, ‘identity’ is clearly a central theme in political discourse and warrants serious analysis. Because individual and group identities are formed ‘in relation to a world beyond themselves’, identity politics are of prime concern to International Relations.2 Huntington provides a provisional definition of identity that acts as a starting point for his argument: people define themselves in terms of ancestry, religion, language, history, values, customs, and institutions, [they] use politics not just to advance their interests but also to define their identity. We know who we are only when we know who we are not and often when we know whom we are against.3